Pesantren’s Traditions in Preparing Human Resources (Santri) at Ibnul Amin Pamangkih and Rasyidiyah Khalidiyah Amuntai Pesantren - Murdan Murdan (Ta'dib: Jurnal Pendidikan Islam, 2020)
This study aimed to know what traditions were developed by Ibnul Amin Pamangkih and Rasyidiyah Khalidiyah Amuntai Pesantren in preparing human resources (santri). This study used field research which was done by observing pesantren’s traditions in preparing human resources (santri) at Ibnul Amin Pamangkih and Rasyidiyah Khalidiyah Amuntai pesantren in preparing human resources (santri). The qualitative approach was used in this study. Then, the data obtained from the interview, observation, and documentation. While, the data sources were from foundation management, the head of pesantren, administrators, ustadz and ustadzah. The result of this study showed that the sciences and skills field were developed at pesantren. Science field covered writing book, reading yellow book, studying Nahwu and Sharaf, and vocabuary memorizing (English and Arabic). While skills field covered foreign language conversation (Arabic and English), reading Maulid, pilgrimage, muhadharah, memorizing Al-Qur’an, memorizing prayers of arwah, haul, and selamat, Haula tradition and calligraphy.